Comprehensive Analysis of The Milkfish Producer's Welfare and The Development of Halal Blue Economy Businesses - Mashudi, Mashudi; Dahruji, Dahruji; Ubudiyah, Hakimatul (LPPPM STAI Darul Hikmah Bangkalan, 2025)
The Junok pindang milkfish product has a distinctive taste, different from other pindang milkfish. However, until now, its production has not been widely developed and is only known from generation to generation. This study was conducted to determine the level of welfare of its producers and the development of businesses based on the halal blue economy. This study used a qualitative methodology. The main data collection used interviews and direct observation. The analysis process used the theory of Miles and Huberman with data collection, reduction, display, verification, and concluding testing of the validity of the data. The results of the study indicate that the welfare of producers is generally achieved through indicators of fulfilling food, clothing, and housing needs, although at the level of fulfilling health and higher education needs, it is still not optimal due to limited infrastructure and public awareness. The development of producer businesses can be seen from the increase in income, quality of life, and the creation of new jobs, but this development has not been fully maximized to support the objectives of developing industrial centers based on the halal blue economy, including the need for assistance in the halal certification of pindang milkfish products